Analisis Flypaper Effect Pada Pemerintah Daerah Di Provinsi Papua - Robert M. WST. Marbun; Ida Ayu Purba Riani; Charley M. Bisai (Universitas Cenderawasih, 2016)
The purpose of this research is to analyze the effect of General Allocation Fund Transfer (DAU) and Local Income (PAD) to local government expenditure (BD) in Papua Province. To determine and analyze how flypaper effect happen to the local government expenditure in Papua Province. This research using panel data in the 26 (twenty six) out of 29 local government in Papua Province in the year of 2010-2013 period. The data gathered from the Regency Expenditure Realization Report on the Fund report of local government that already get into final audit from BPK RI and submitted to the DJPK Ministry of Finance of The Republic of Indonesia and Papua in Figures that published by Central Bureau Of Statistics. This research results show that PAD and DAU at the same time positively affect the local government expenditure (BD) in Papua Province; but only DAU coefficient affects significantly and having a positive relation to the regency expenditure, while PAD statisticaly not significant to the local government expenditure in Papua Province. Coefficient value of DAU is higher than the PAD even though only the DAU is signifficant, this thing shows flypaper effect has detected happen on the local government expenditure in Papua Province.Keywords: Flypaper Effect, General Allocation Fund, DAU, PAD.